Do Prado ao Mineirão: a história dos estádios na capital inventada - Georgino Jorge de Souza Neto (2017)
This study aims to investigate the movement and the context that allowed the building of the main football stadiums in the city of Belo Horizonte-MG, and how these legitimize themselves from thThis study aims to investigate the movement and the context that allowed the building of the main football stadiums in the city of Belo Horizonte-MG, and how these legitimize themselves from the dialogue established with their social surroundings, in a wide array of aspects (economic, politic, cultural, among others). For that matter, the period limited for the investigation covered the years from 1904 to 1965, for sheltering the time in which the stadiums were erected in the city´s landscape. For representing one historiographic investigation, the study has based itself methodologically in two theoretical approaches: the Cultural History, particularly the notion of representation developed by Roger Chartier, and the Micro- History, notoriously the paradigm concept described by Carlo Ginzburg. This way, the search sources privileged the periodicals. Thus, newspapers and magazines from that time were used to enable the harmony of the proposed plot. Accordingly, the chapters were structured in specific time cuts, hence: the built of Prado Mineiro and its appropriation by football (1904-1923); the stadiums that appeared in the 1920´s and go through important reconstruction in the 1940´s, bond to the Sete de Setembro club and the important football space, distinctively in its relation with the 1950 (1948-1950) World Cup; and, finally, the Mineirão stadium, main stage of football in the city since its opening up to current days (1958-1965). The evidences point to the identification of three particularly punctual understandings: the first concerns the relation established between these stadiums and the urban/spatial structuring in their surroundings, promoting and/ or provoking rearranges related to both urban mobility, the building of access ways, traffic planning, logistics improvement etc. In all these moments, this relation is extremely powerful, enabling the noticing of an influx of the city spatial organizing due to the existence of the stadiums. Another comprehension deals with how much these spaces configure themselves within the modernity logic, providing (or trying to) to the demands and requests of another social order, since urbanistic aspects to the spetacularization of the sport-related phenomenon and its threading to a growing market determination. The idea of modernity is configured, then, as an important relational category of such stadiums with the city of Belo Horizonte, establishing, in a way, the legitimizing convincing of its construction. At last, the manner of how the stadiums in Belo Horizonte are strongly marked by political context throughout the whole time lapse of this study. From Prado to Mineirão, the political order is determining to the condition of execution of the projects that originated stadiums, from political opponents rallies and quarrels, certain groups privileges concerning the sporting field in town, and the elaboration of an easy-making legislation for implementing such spaces.